The Effect of Service Quality on Citizen’s Expectation through Dimension of Tangible, Emphaty, Reliability, Responsiveness and Assurance (TERRA) - Irma Idayati; Indrawati Mara Kesuma; Ronal Aprianto; Suwarno Suwarno (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
The objective of this research is to find out the highest percentage of respondents' answers from the level of service quality as measured by the level of reality and expectations of the community according to the dimensions of Tangible, Emphaty, Reliability, Responsiveness, and Assurance (TERRA) of each service in the environment of Lubuklinggau municipal government. Based on the results of the calculation of the frequency of service quality variables on the reality and expectations of the community, all dimensions of service quality are show that on the average community answers satisfied while viewed from the expectations of the average community the answer is very important. The results of the Chi-Square calculation of service quality variables Towards the reality and expectations of the community seen from the Tangible, Reliability and Responsiveness of the Chi-Square calculation results of all Offices / Agencies there is no difference in Tangible dimensions to the reality and expectations of the community, it's just that the Office of National Unity and Politics of Lubuklinggau has differences in the dimensions of Tangible, Reliability and Responsiveness to the realities and expectations of society as well as seen from Emphaty and Assurance: the results of the Chi-Square calculation of all Offices / Agencies, there is no difference in the dimensions of Emphaty and Assurance to the reality and expectations of society.